Influence of almond hulls in lamb diets on animal performance and meat quality. (October 2022) - Scerra, Manuel; Bognanno, Matteo; Foti, Francesco; Caparra, Pasquale; Cilione, Caterina; Mangano, Fabrizio; Natalello, Antonio; Chies, Luigi
Abstract: Almond hulls (AH) were fed to lambs to study effects on performance and meat quality. Thirty Sarda lambs were allotted to three experimental groups and fed for 40 days either a cereal-based concentrate diet (control) or diets in which cereals were replaced with 15% (AH15) or 30% (AH30) almond hulls on a DM basis. Diets did not affect final body weight, dry matter intake, average daily gain, feed conversion ratio or carcass weight. Replacing part of the cereal mix (i.e., barley and maize) with AH did not affect meat fatty acid profiles. After 5 and 7 days of refrigerated storage respectively for cooked and raw meat, AH15 and AH30 treatments reduced meat lipid oxidation ( P  < 0.001). Our results suggest feeding almond hulls up to 30% in fattening lamb diets can improve meat oxidative stability without compromising growth performance. Highlights: Almond hulls did not affect intramuscular fatty acids composition. Inclusion of almond hulls does not compromise animal performances. The integration of almond hulls reduced lipid oxidation in meat.